Standardization of cryopreservation in coconut (Coconut nucifera) plumule based on vitrification technique using V-cryomesh - Aparna Veluru; Mohamed, Neema; Krishna Prakash; Fathimath Zaeema M P; Sudha R; Muralikrishna KS (Current Horticulture, 2025)
A technique was tried for cryopreservation of coconut (Cocos nucifera L.) plumular regions based on vitrification technique using aluminium V-cryomesh as an anchoring material. Coconut plumular regions, excised from mature zygotic embryos, were pre-cultured in a solid Y3 medium supplemented with 0.2 M to 0.6 M sucrose. After pregrowth, explants were treated with loading solution (Y3 medium with 0.4 M sucrose + 2 M glycerol) and transferred to V-cryomesh and embedded using calcium alginate. Explants adhered to V-cryomesh were subjected to dehydration using PVS3 (40 minutes) and transferred to cryovials for storing in liquid nitrogen. After 48hr of liquid nitrogen treatment, material was thawed at 40ᵒC for 2 minutes and later treated with unloading solution for 30 minutes and explants were inoculated to retrieval media. The optimal protocol involved preculture of plumules for 72 hr on medium with 0.4 M sucrose followed by PVS3 treatment for 40 minutes, rapid cooling and rewarming and treating with unloading solution for 30 minutes. Under these conditions, 33% post thaw recovery and 7% plantlet recovery was observed. Accommodation of smaller sized explants in large number and easy handling were the major advantages of cryomesh. The method can be useful for conservation of valuable coconut germplasm in the form of plumules.